2016
DOI: 10.1002/ab.21658
|View full text |Cite
|
Sign up to set email alerts
|

How do different dimensions of adolescent narcissism impact the relation between callous‐unemotional traits and self‐reported aggression?

Abstract: The current study examined the moderating influence that different aspects of narcissism have on the relation between callous-unemotional (CU) traits and aggression in a sample of 720 adolescents (500 males), ages 16-19 enrolled in a 22-week residential program. Findings from the two studies revealed that psychopathy-linked narcissism as assessed by the Antisocial Process Screening Device (APSD; Frick & Hare, 2001; Antisocial process screening device. Toronto: Multi-Health Systems.) and vulnerable narcissism a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 72 publications
3
22
0
Order By: Relevance
“…As noted, previous research demonstrated that when youth exhibit both high levels of CU traits and psychopathy‐linked narcissism or vulnerable narcissism, they are more likely to engage in higher levels of aggression (see Lee‐Rowland et al, 2017). Notably, normal narcissism did not have the same effect.…”
Section: Introductionmentioning
confidence: 87%
See 4 more Smart Citations
“…As noted, previous research demonstrated that when youth exhibit both high levels of CU traits and psychopathy‐linked narcissism or vulnerable narcissism, they are more likely to engage in higher levels of aggression (see Lee‐Rowland et al, 2017). Notably, normal narcissism did not have the same effect.…”
Section: Introductionmentioning
confidence: 87%
“…Aggression may be one such strategy that individuals high in narcissism use to rebuild their self‐esteem and sense of superiority over others if these self‐perceptions have been threatened (Morf & Rhodewalt, 2001). Psychopathy‐linked narcissism (Barry et al, 2007; Kerig & Stellwagen, 2010), normal narcissism (e.g., Barry, Kauten, & Lui, 2014), and pathological narcissism (Barry & Kauten, 2014; Lee‐Rowland, Barry, Gillen, & Hansen, 2017) have all been associated with youth aggression. Moreover, different aspects of narcissism may translate to aggression in adolescents from different processes.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations